Collaborative system: higher education search engine - Abdul Wahid, Al- Abrar; Aboubakar Idriss, Hissein; Adam Labab Ali, Muhanad; Ahmad Dahlan, Abdul Rahman (3KBioXML Publishers Pakistan, 2011)
Malaysian universities or colleges has been one of the main attractive educational destinations to foreigners for the last decade. Malaysian educational institutions are recognized in opening doors of knowledge that fulfill student’s lives with skills, awareness and enthusiasm. There are over 20 public universities and 60 private colleges that offer a complete range of programs leading to highly regarded and internationally recognized qualifications. Despite the vast information made available by these institutions on their websites, majority of potential students face challenges in choosing the right program, courses and university that suits their needs. This research study the innovative method which could be developed and leveraged by the educational industries, specifically the Ministry of Higher Education Malaysia (MOHE) in close collaboration with these universities and colleges, in using search engine comparator technology whereby assisting potential students in making selection. The study raises awareness of relevant collaboration initiatives that could be adopted and replicated to facilitate students and parents in making well-informed decision.